Malawi - Mutual Evaluation Report : Anti-Money Laundering and Combating the Financing of Terrorism - World Bank (Washington, DC, 2012)
Malawi is a land-locked country. It is bordered by Zambia to the north-west, Tanzania to the north and Mozambique, which surrounds it on the east, south and west. This Report provides a detailed assessment of the Anti-Money Laundering AML/Combating the Financing of Terrorism CFT measures in place in Malawi as of May 11, 2008, two months after completion of the on-site mission. It describes analyses and makes an assessment of the measures and systems in place as of that date, and provides recommendations on how certain aspects of the system could be strengthened. This report provides a detailed assessment of the level of compliance, and provides recommendations to improve compliance with the prevailing context of Malawi. The government of Malawi has demonstrated a high level of commitment to establishing a strong AML/CFT framework. This commitment is reflected by the enactment of the Money Laundering proceeds of serious crime and Terrorist Financing act in August 2006 (ML and TF Act) and the beginnings of an implementation program. Finally, in order to ensure the effective implementation of the ML and TF framework, building the technical AML capacity/knowledge of law enforcement agencies, the public prosecutors and the judiciary will be critical.